Process evaluation of maternal health service at outreach sites during health and nutrition day (Mamta day) in urban slums of Western India - Mehta, Kedar G.; Pandya, Chandresh M.; Solanki, Dipak M. (International Journal Of Community Medicine And Public Health, 2017)
Background: The concept of health and nutrition day (Mamta Divas) evolved under Reproductive & child health programme to strengthen the outreach maternal and child health services. So the current study was conducted to monitor the antenatal care services provided at outreach sites during Mamta Divas by urban health centers in slum areas of Vadodara in Western India. Methods: A cross sectional study was conducted to include one randomly selected outreach session from all of the 17 urban primary health centers of Vadodara city from April-2013 to March-2014. 17 session sites were observed for process evaluation of three components of maternal health care viz, availability of ‘service providers’, ‘equipment’s and supplies’ and ‘direct observation of actual service provision’ at the site using a structured checklist. Results: Out of 17 session sites visited, auxillary nurse midwife was present at 14 sites but health supervisors were not present at any site. Most of the equipments and supplies were present at all sites but Iron folic acid tablets were observed at 9 sites only. Antenatal history taking, weighing of the pregnant woman, injection tetanus toxoid was done at all sites but correct blood pressure measurement and hemoglobin estimation was observed at 4 and 3 sites respectively. Abdominal examination was not observed at any site. Conclusions: Antenatal services like registration of antenatal women, their weighing and providing tetanus toxoid were mainly focused but other services like identification of high risk pregnancy, abdominal examination, blood pressure measurement and hemoglobin estimation needs to be strengthened during Mamta divas.